Historical Vignette: Attempted treatment of Sigmund Freud's oral squamous cell carcinoma by vasectomy (Steinach Operation) in 1923. (29th November 2019) - Benmoussa, Nadia; Charlier, Philippe; Rebibo, John‐David
Abstract: Background: At the beginning of the 20th century, the Viennese physiologist Eugen Steinach proposed to treat the effects of physiological ageing by vasectomy. After experimenting his theory with animal, he published his results, and convinced scientists to apply this method to humans (ie men). The scientific community has been convinced by these pictures of the interest of these vasectomies, and many patients undergo it for the purpose of physical, mental and sexual rejuvenation, including Sigmund Freud. Objectives: The aim of this study is to explain How Sigmund Freud decided to do this operation. Materials and methods: We read and analysed a set of articles and books about Sigmund Freud live and the rejuvenation theory with the help of Sigmund Freud Museum (London). Results: Freud suffered from a cancer of the right maxillary diagnosed in 1923 for which he underwent a first surgery of excision on April 20, 1923 followed by radiotherapy and a lot of another surgery to treat reccurences. Probably in despair or wanting to heal himself, he decided to have a Steinach vasectomy. Discussion: Sigmund Freud knew Steinach's theories through his scientific publications, including his work on the «treatment of homosexuality» ( sic !); he even tended to believe that biological methods were more reliable for «treating homosexuality» than his psychoanalyses. Because cancer was considered a disease of old age, vasectomy rejuvenation seemed to be useful (and potentially effective) in treating cancer, according to Freud. Conclusion: Even Sigmund Freud, who was a great scientist, was fooled by the scientific results of a badly conducted study. We must keep a critical eye on new medical developments.